Impact of Intervention on Healthcare Waste Management in a Reference Laborator - Qasim, Javeria; Gill, Maria Mushtaq; Mirza, Irfan Ali; Riaz, Muhammad Omair; Naqvi, Sakeenah Hussain; Sajjad, Rabia (Pakistan Armed Forces Medical Journal, 2025)
Objective: To assess the effect of interventions on knowledge and practices of healthcare staff regarding healthcare waste management, in the department of Microbiology, Armed Forces Institute of Pathology, Rawalpindi.Study Design: Quasi-experimental studyPlace and Duration of study: Department of Microbiology, Armed Forces Institute of Pathology, Rawalpindi Pakistan, from July-December 2022Methodology: This study was conducted over 33 participants including laboratory technologists, sanitary workers and Medical laboratory technology (MLT) students. The baseline knowledge and practices were checked by using an “Awareness questionnaire” and an “Observation checklist” respectively. Interventions included lectures, posters and on-spot checks. The same questionnaires were used to assess the post-intervention knowledge and practices. The pre-and post-intervention awareness scores were compared using and a p-value of